2014
DOI: 10.1097/ijg.0b013e318286ffa5
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Nerve Fiber Layer Measurements by Scanning Laser Polarimetry With Enhanced Corneal Compensation in Healthy Subjects

Abstract: Age significantly affected all RNFL measurements with the ECC protocol of SLP, whereas TSS and residual anterior segment retardance affected the overall average and the superior average RNFL measurements, respectively. Axial length and corneal birefringence measurements did not influence any RNFL measurements. RNFL measurements had good intrasession repeatability. These results are important while evaluating the change in structural measurements over time in glaucoma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…Previous studies have reported this using the VCC protocol of SLP (Bagga et al 2005;Da Pozzo et al 2006). We have also reported the same previously using the ECC protocol of SLP in normal subjects even when the TSS values were within the acceptable limits (Rao et al 2013). We had found that the TSNIT average measurements were significantly higher at low TSS values.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…Previous studies have reported this using the VCC protocol of SLP (Bagga et al 2005;Da Pozzo et al 2006). We have also reported the same previously using the ECC protocol of SLP in normal subjects even when the TSS values were within the acceptable limits (Rao et al 2013). We had found that the TSNIT average measurements were significantly higher at low TSS values.…”
Section: Discussionsupporting
confidence: 57%
“…We also ran the entire analysis using a control group consisting of eyes with no suspicious findings for glaucoma. The characteristics of this control group have been detailed earlier (Rao et al 2013). The results of the ROC regression analysis remained similar with TSS significantly affecting the AUCs of TSNIT average (coefficient: 0.08, p value: 0.001) and inferior average parameters (0.06, 0.007) but not NFI (0.02, 0.39) and superior average parameters (0.01, 0.71).…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…6,8,12 Our procedure of SLP imaging has also been reported earlier. 13 In brief, a corneal scan was obtained first to measure the corneal birefringence. RNFL was imaged later using a single-scan protocol.…”
Section: Methodsmentioning
confidence: 99%